2007
DOI: 10.1080/00365540600993285
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in infective endocarditis: Pre- and co-morbid conditions lead to different management and outcomes in female patients

Abstract: The impact of gender on the presenting characteristics, management, and outcomes in infective endocarditis (IE) has not been adequately studied. The goal of our study was to better understand differences in management and outcome of IE between genders. Data were obtained prospectively from 439 patients in the Duke Endocarditis Database from 1996 to 2004. Baseline characteristics of patients were examined using univariable analysis. Variables associated with gender, in-hospital surgery and long-term mortality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
45
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 21 publications
8
45
5
6
Order By: Relevance
“…Compared with the two major publications about sex differences in IE,7 10 our findings are similar in terms of women's demographics and baseline characteristics: women with IE are older than men, more often on haemodialysis and more often have a mitral valve IE. In all three studies, women underwent EVS less often than men.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Compared with the two major publications about sex differences in IE,7 10 our findings are similar in terms of women's demographics and baseline characteristics: women with IE are older than men, more often on haemodialysis and more often have a mitral valve IE. In all three studies, women underwent EVS less often than men.…”
Section: Discussionsupporting
confidence: 71%
“…In their study performed in 439 patients (187 women), Aksoy et al found that female sex was associated with a lower rate of EVS but was not associated with mortality after adjustment for confounding factors. The authors suggested that sex difference in the rate of EVS resulted mainly from pre-existing and/or coexisting conditions such as diabetes, haemodialysis and chronic immunosuppression, which were more frequent in women 7. The study by Sambola et al , performed on 271 patients (88 women), found different results.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, female patients may have a worse prognosis and undergo valve surgery less frequently than their male counterparts. 27 Types of infective endocarditis IE should be regarded as a set of clinical situations which are sometimes very different from each other. In an attempt to avoid overlap, the following four categories of IE must be separated, according to the site of infection and the presence or absence of intracardiac foreign material: left-sided native valve IE, left-sided prosthetic valve IE, right-sided IE, and device-related IE (the latter including IE developing on pacemaker or defibrillator wires with or without associated valve involvement) ( Table 3).…”
Section: Incidence Of Infective Endocarditismentioning
confidence: 99%
“…Infective endocarditis is sometimes complicated with infective emboli to lung, spleen, kidney and brain. The point is that early diagnosis is essential [11], sometime surgical interventions or also valve replacement is required [8]. In our patient also due to severity of mitral valve involvement, it was replaced with a metal one.…”
Section: Discussionmentioning
confidence: 99%
“…The physician must have a good clinical insight for diagnosing and choosing of better diagnostic method like TEE in his or her approach to disease [10]. TEE in comparison with TTE gets better quantitative and qualitative data regarding presence of IE and level of value dysfunction [11]. Staphylococci and streptococci are the most frequent germs and medication for covering of both of them was started initially (due to clinical suspicious) [8].…”
Section: Discussionmentioning
confidence: 99%